Authentic leadership as a predictor of resilience, humility, and compassion of subordinators - Gomes, Sofia (2021)
The present research is based on a questionnaire applied to 109 employees of Portuguese companies, who, in the performance of their professional activity, are in a position of direct subordinates of the top management of these companies and analyses the relationship between authentic leadership and its employees' resilience, humility, and compassion. This research empirically validates the theoretical arguments that suggest that authentic leadership is related to resilience, humility, and compassion (the latter, measured based on the dimensions of kindness, common humanity, mindfulness, indifference, disengagement, and separation) and demonstrates that subordinates are crucial resources to help organisations face competitive challenges, taking advantage of their employees' potential and promoting organisational efficiency and competitive advantages over the competition.